Paradigma Pemikiran Ibnu Khaldun tentang Pendidikan dan Relevansinya dalam Sistem Pendidikan Modern - Yaqin, Mokhammad Ainul (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2025)
Abstract Purpose: Ibn Khaldun’s thought positions education as a holistic process aimed at developing intellect, moral character, social skills, and civilization. Its relevance remains very strong in contemporary educational systems, particularly in strengthening character education, promoting a humanistic approach, and fostering education that is adaptive to the needs of the times. Design/methodology/approach: “This study employs a qualitative approach through an examination of primary sources, followed by a comparison between classical Islamic educational thought and contemporary educational theories.” Research limitations/implications: This study presents several important implications for the development of modern education. First, the concept of balance between theory and practice emphasized by Ibn Khaldun provides a foundation for designing curricula that are more adaptive and applicable. Such curricula are increasingly relevant amid the demands of the global labor market, which prioritizes practical skills. Findings: The research findings indicate that Ibn Khaldun’s comprehensive approach, which integrates moral, intellectual, and practical skill aspects, offers an important perspective for addressing various contemporary educational challenges, including the strengthening of critical thinking skills and preparedness for the dynamics of the global era. Overall, Ibn Khaldun’s educational thought remains highly relevant, particularly in shaping well-rounded individuals and in designing learning systems that are flexible and responsive to change. Originality/value: “The originality of Ibn Khaldun’s educational thought lies in his bold integration of intellectual, moral, social, and historical dimensions into a unified educational framework. The originality of studies on its relevance lies in the effort to contextualize this classical thought in order to address contemporary educational challenges in a systematic and practical manner